Matter wave optics perspective at molecular photoionization: K-shell photoionization and Auger decay of N2 - Schöffler, M. S.; Jahnke, T.; Titze, J.; Petridis, N.; Cole, K.; Schmidt, L. Ph H.; Czasch, A.; Jagutzki, O.; Williams, J. B.; Cocke, C. L.; Osipov, T.; Lee, S.; et al. (My University, 2011)
In this paper, we shed new light on the molecular photoionization of a diatomic molecule. We will elaborate the differences and analogy between a quantum optical and light–matter interaction approach in a study of K-shell photoionization of N2 in which the photoelectron and the subsequently emitted Auger electron are both measured in coincidence in the body fixed frame of the molecule. The two electrons form an entangled state inside a double slit. By changing the photon energy we create different types of interference in the photoelectron and the Auger electron wave.